CHARACTER EDUCATION METOD FROM THE LENS OF AL-GHAZALI ON GENERATION Z - Reni Sasmita (Edusoshum : Journal of Islamic Education and Social Humanities, 2022)
The moral significance of Generation Z pupils is the issue in this study. This is illustrated by the numerous activities outside the norm displayed by Generation Z students, including using educational drugs, student brawls, and a lack of respect for lecturers, parents, and even society. This is due to using and applying an ineffective value education strategy for kids. Researchers will look at how to teach the values of the Al-Ghazali method to generation Z in this project. This research aims to describe Al-value Ghazali's teaching in the generation Z period. This study employs a library research strategy. According to the conclusions of this study, Al-Nilai Ghazali's teaching style is consistent with Islamic education in the generation Z age. Al-Ghazali uses visuals, stories, guidance and training methods, and habituation methods to teach values education. He outlines a character education technique particularly relevant to Generation Z pupils. Al-Ghazali uses illustrative methods, stories, counsel and training, and habituation methods to teach value education.